Sosialisasi Pentingnya Menabung Sejak Usia Dini pada Anak Sekolah Dasar Desa Sihuik-Huik - Anisa Madani Nasution; Siti Aisyah; Serly Charita Harahap; Lili Cahayani Hasibuan (Jurnal Pengabdian Masyarakat Waradin, 2026)
The Community Service Program (KKN) is a tangible form of student service to the community as an implementation of the three pillars of higher education, namely education, research, and community service. One of the activities carried out during the KKN in Sihuik-huik Village was to socialize the importance of saving from an early age to sixth grade students at MIS Al-Abraar. This activity aimed to instill an understanding of the concept of saving, its benefits, and to train students’ skills through the practice of making piggy banks from used bottles. The implementation methods included delivering material using PowerPoint, showing simple animations, and creative practice in decorating piggy banks. The results of the activity showed a positive response from the students, who were enthusiastic from the beginning to the end of the program. The students not only understood the importance of saving money, but were also motivated to practice it by using the piggy banks they had made themselves. In addition to training creativity and environmental awareness, this activity also instilled the values of discipline, independence, and religious awareness that saving is part of Islamic teachings in managing wealth wisely and avoiding wastefulness. Thus, this socialization activity proved to be effective as a simple financial education medium that shaped positive and beneficial attitudes for the students’ future preparation.